Therapeutic Assessment of Diverse Doxycycline-Based Formulations in Promoting Deep Corneal Wound Healing: Evidence from a Rat Model - Sze-Min Chan; Ching-Li Tseng; Wei-Hsiang Huang; Chung-Tien Lin (Veterinary Sciences)
Doxycycline (Dxy), a broad-spectrum antibiotic with anti-inflammatory effects, is commonly used in ophthalmology but is unstable as a topical eyedrop, degrading quickly into inactive forms and requiring frequent application. To address this, gelatin nanoparticles (GNPs) loaded with Dxy (DNPs) were developed as a stable ophthalmic nanomedicine for enhancing corneal wound healing by inhibiting matrix metalloproteinases (MMPs). In this study, female Sprague–Dawley rats underwent lamellar keratectomy, and various Dxy formulations—oral, conventional eyedrops, and DNP-containing eyedrops—were evaluated for corneal wound repair. Clinical assessments included fluorescein staining, slit-lamp biomicroscopy, spectral-domain optical coherence tomography (SD-OCT) imaging, histopathology, and immunohistochemistry for MMP-2, MMP-9, and α-SMA. The DNP group (0.01% Dxy in DNPs, applied twice daily) demonstrated faster corneal thickness recovery and epithelial healing on days 7 and 14 compared to 0.1% Dxy eyedrop treatments applied twice or four times daily. DNP-treated eyes also showed reduced angiogenesis intensity and lower MMP-2 and MMP-9 immunoreactive scores, with enhanced stromal recovery and reduced neovascularization. These results highlight DNPs’ potential as a superior treatment for corneal wounds, providing effective healing with less frequent dosing and lower drug concentrations. This study supports DNPs’ potential for clinical application as a stable and efficient therapeutic agent in ophthalmology.